Report of patients with chronic myeloid leukemia, from hematology clinic, Ahmedabad, Gujarat 2000-2010 at 1 st myelostone meeting: Indian evidence of chronic myelogenous leukemia - Uday R Deotare; Urmish Chudgar; Eva Bhagat (Indian Journal of Medical and Paediatric Oncology)
The data of 156 patients was presented from Hematology clinic, Ahmedabad. This hematology clinic caters large number of the population from Gujarat as well as from neighboring states such as Rajasthan and Madhya Pradesh. Out of 156 patients, 146 (94%) patients were in chronic phase. Complete hematological response was seen in 90% of patients and overall survival was 82% at 5 years.